GLANCING METEOR SHOWER OVER INDONESIA: VOLATILITY SPILLOVERS FROM A MAJOR STOCK MARKET TO INDONESIAN STOCK MARKET AND CURRENCY - Sekar Utami Setiastuti (Faculty of Economics and Business, Universitas Gadjah Mada, 2011)
During the deepest financial crisis in mid 2007-2009, increasing volatility of Indonesian stock market index were captured. Increasing volatility of the series is acommon event since the volatility of financial market around the globe is increasing likewise. Yet, whether it is a sign of volatility spillover or comovement still emerges as amystery.This paper seeks to explain the causes of the increasing volatility in domestic currency and stock market. To investigates the hypothesis in tranquil and crisis periods, theobservation period of January 2, 2003 to May 31, 2010 is splitted into two sub-periods with different levels of volatility. Using VAR-EGARCH on daily stock market index of Indonesia (IDX), S&P 500, and the bilateral exchange rate, we documented the existence of meteor shower and heatwaves in Indonesia stock market and exchange rate during crisis period. This finding implies that in crisis period, Indonesian stock market and exchange rate volatility were not only affected by market specific factors, but were alsoaffected by volatility of the major stock market. We also captured asymmetric affects in the model which suggests that negative shock in the major stock market will increase the volatility of domestic stock market more than positive shock will.Keywords: volatility spillovers, comovement, contagion, VAR-EGARCH